Use of Carbon and Basalt Fibers with Adhesives to Improve Physical and Mechanical Properties of Laminated Veneer Lumber - Mario Núñez-Decap; Bárbara Sandoval-Valderrama; Camila Opazo-Carlsson; Boris Moya-Rojas; Marcela Vidal-Vega; Alexander Opazo-Vega (Applied Sciences, 2023)
Climate change is one of the main factors influencing the research of environmentally friendly materials. This is why the use of engineering fibers as a reinforcement technique in wood, in order to increase its mechanical properties, has recently been investigated. This research presents the results obtained from the use of carbon and basalt fiber fabrics as a reinforcement for microlaminated Radiata Pine wood panels at a laboratory scale using the adhesives epoxy resin and polyvinyl acetate. Tests were carried out in comparison to the control boards, relating the physical properties obtained in terms of thickness swelling by 48 h-water immersion with a decrease of 19% for the polyvinyl acetate and carbon fiber matrix reinforcement, about the mechanical properties evaluated, a better performance was obtained for the epoxy resin and carbon fiber matrix reinforcement and in terms of flexural stiffness and strength (in flatwise), tensile strength and Janka hardness, with an increment of 31%, 38%, 56% and 41%, respectively.